Acute sleep deprivation disrupts emotion, cognition, inflammation, and cortisol in young healthy adults - Thompson, Kayla I.; Chau, Minh; Lorenzetti, Margaret S.; Hill, Lauren D.; Fins, Ana I.; Tartar, Jaime L. (Frontiers in Behavioral Neuroscience, 2022)
Chronic sleep deprivation has been demonstrated to diminish cognitive performance, alter mood states, and concomitantly dysregulate inflammation and stress hormones. At present, however, there is little understanding of how an acute sleep deprivation may collectively affect these factors and alter functioning. The present study aimed to determine the extent to which 24-hours of sleep deprivation influences inflammatory cytokines, stress hormones, cognitive processing across domains, and emotion states. To that end, 23 participants (mean age = 20.78 years, SD = 2.87) filled out clinical health questionnaires measured by the Pittsburgh Sleep Quality Index, Morningness Eveningness Questionnaire, and Center for Epidemiological Studies Depression Scale. Actigraph was worn for 7 days across testing to record sleep duration. At each session participants underwent a series of measures, including saliva and blood samples for quantification of leptin, ghrelin, IL-1β, IL-6, CRP, and cortisol levels, they completed a cognitive battery using an iPad, and an emotion battery. We found that an acute sleep deprivation, limited to a 24 hr period, increases negative emotion states such as anxiety, fatigue, confusion, and depression. In conjunction, sleep deprivation results in increased inflammation and decreased cortisol levels in the morning, that are accompanied by deficits in vigilance and impulsivity. Combined, these results suggest that individuals who undergo 24hr sleep deprivation will induce systemic alterations to inflammation and endocrine functioning, while concomitantly increasing negative emotions.